Harnessing DLL3 inhibition: From old promises to new therapeutic horizons - Cortinovis, Diego Luigi; Colonese, Francesca; Abbate, Maria Ida; Sala, Luca; Meazza Prina, Marco; Cordani, Nicoletta; Sala, Elisa; Canova, Stefania (Frontiers in Medicine, 2022)
Small-cell lung cancer (SCLC) is an aggressive neuroendocrine tumor with a high relapse rate, limited therapeutic options, and poor prognosis. The combination of chemotherapy and immune-checkpoint inhibitors leads to a new therapeutic era even if the lack of predictive biomarkers of response reduces the effectiveness in applying the treatment to the entire population of SCLC patients. The lack of treatments able to bind to a specific target has always been a substantial difference compared to the non-small cell lung cancer (NSCLC) counterpart. Delta-like canonical Notch ligand 3 is a protein frequently overexpressed in SCLC and is therefore being explored as a potentially promising therapeutic target in high-grade neuroendocrine lung cancers. In this article, we critically review the activity and efficacy of older antibody-drug conjugate (ADC) DLL3 inhibitors with their relative failures through the new compounds and their possible applications to clinical practice with particular attention to a new molecular SCLC classification.